2019
DOI: 10.1186/s12944-019-0977-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipids composition and metabolism in colorectal cancer: a review

Abstract: Altered metabolism of lipids is currently considered a hallmark characteristic of many malignancies, including colorectal cancer (CRC). Lipids are a large group of metabolites that differ in terms of their fatty acid composition. This review summarizes recent evidence, documenting many alterations in the content and composition of fatty acids, polar lipids, oxylipins and triacylglycerols in CRC patients’ sera, tumor tissues and adipose tissue. Some of altered lipid molecules may be potential biomarkers of CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(224 citation statements)
references
References 228 publications
6
209
0
Order By: Relevance
“…The results of some observational studies suggest that dietary provision of n-3 polyunsaturated FAs (PUFAs) from marine food sources might mitigate CRC risk and reduce mortality associated with this malignancy [8]. However, other authors found no link between n-3 and n-6 PUFAs and CRC development or treatment outcomes [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results of some observational studies suggest that dietary provision of n-3 polyunsaturated FAs (PUFAs) from marine food sources might mitigate CRC risk and reduce mortality associated with this malignancy [8]. However, other authors found no link between n-3 and n-6 PUFAs and CRC development or treatment outcomes [9].…”
Section: Introductionmentioning
confidence: 99%
“…An altered lipid composition can have a major impact on survival, proliferation or communication of tumor cells, due to the multiple roles of lipids in cellular signaling, build-up of cell membranes or in cell-to-cell interactions [20,38]. CRC development has been shown to be associated with a number of lipid alterations (reviewed in [39]), including increasing amounts Table 2 71 (1.1-2.64 .72 (1.19-2.47 of some PLs in transformed cells [40][41][42]. For example, Li et al established correlations of increased PI and PC with CRC genesis, as well as the relationship between increased PE and hepatic metastasis in colorectal carcinoma [43].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism is regulated by complex signaling networks in CRC tumor cells, which are closely related to cell growth, proliferation, differentiation, survival, and apoptosis (39). Several studies have indicated that some fatty acid metabolism pathways are associated with the development and progression of colorectal adenocarcinoma (40, 41). Beatriz et al also showed that changes in fatty acid metabolism are a crucial factor in the progression from colorectal adenoma to adenocarcinoma (42).…”
Section: Discussionmentioning
confidence: 99%